Alfabetização digital na biblioteca pública : fortalecendo sua função social para mitigar a exclusão digital - Moura, Mariana Silva (2024)
The research investigates the role of public libraries in promoting Digital Literacy to address digital exclusion, emphasizing their social responsibility and alignment with the UN Sustainable Development Goals (SDGs). The objective is to evaluate the implementation of theoretical guidelines and the global consistency of progress in Digital Literacy. Using a multi-method approach, the research includes a qualitative and bibliographic dimension with a systematic review; and an exploratory dimension with the investigation of Digital Literacy initiatives in libraries worldwide. It also adopts a quantitative perspective when developing bibliometric indicators to analyze scientific production, aiming for a comprehensive and multifaceted understanding of the current state of Digital Literacy in the library context. The systematic review of 43 scientific articles reveals challenges such as the lack of training of information professionals and the need for adequate investment in public libraries. Still, it highlights the crucial role of these institutions in promoting digital inclusion. The studies analyzed address the future of digital literacy and the application of theoretical frameworks to deal with emerging social issues, such as exclusion from the digital labor market and digital inequality. In developed countries, there is a notable increase in studies on digital learning among elderly and middle-aged adults. In countries with public investment difficulties, actions focus on community practices. Various forms of digital literacy are identified, reflecting a growing concern about the digital exclusion of marginalized groups. Practical activities in world-leading libraries include workshops on device use, guidance on configuration and use of tools, web security workshops, work tools courses, and digital inclusion programs for different demographic groups. In general, the programs identified are aimed at basic computing, with a special focus on continuing education, digital security, awareness, inclusion, accessibility, and a concern for the future of work. The actions show a significant intersection between literature and practice, proving a commitment to digital inclusion and accessibility, especially in contexts marked by technological obstacles and informational vulnerabilities. Three factors are identified: digital literacy is more common in well-funded libraries; most activities focus on basic digital skills, but there is a demand for more advanced programs; and nations’ digital plans are advancing, driven by economic motivations. It is concluded that, although there are efforts to reduce the digital divide by promoting basic digital skills, it is essential to expand access to advanced digital literacy to address complex issues such as critical thinking about technology and the impact of artificial intelligence. Such a measure is crucial to prevent less developed countries from facing a scenario of digital illiteracy, which could lead to a significant increase in underemployment or even absolute unemployment. Moving beyond training for the job market, exploring digital citizenship and social evolution in a world influenced by artificial intelligence, is essential.